Discovery of a Novel Benzenesulfonamide Analogue That Inhibits Proliferation and Metastasis Against Ovarian Cancer OVCAR-8 Cells - Jia Y; Li M; Cao Y; Feng W; Li X; Xue W; Shi H (Dove Medical Press, 2020)
Yanyan Jia, Meijuan Li, Yuan Cao, Wenlong Feng, Xueru Li, Wenhua Xue, Huirong Shi Department of Gynecology and Obstetrics, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, People’s Republic of ChinaCorrespondence: Yanyan JiaDepartment of Gynecology and Obstetrics, The First Affiliated Hospital of Zhengzhou University, Jianshe East Road, Zhengzhou 450052, People’s Republic of ChinaEmail jiayy2019@163.comBackground: Ovarian cancer has been a salient public health concern in the world. It is necessary to develop novel antitumor drugs to treat ovarian cancer.Purpose: This study investigated the synthesis, antiproliferation ability, antitumor mechanisms in vitro and in vivo of a novel benzenesulfonamide derivative.Methods: The novel benzenesulfonamide-1,2,3-triazole hybrid 7c was synthesized from 4-fluorobenzenesulfonyl chloride, prop-2-yn-1-amine and 1-(azidomethyl)-3-phenoxybenzene. The structure of this benzenesulfonamide-1,2,3-triazole hybrid 7c was confirmed by 13C NMR, and 1H NMR. Compound 7c was evaluated for its antitumor effects in vitro and in vivo against ovarian cancer OVCAR-8 cells.Results: We discovered that the benzenesulfonamide hybrid 7c potently inhibited cell proliferation against ovarian cancer. Especially, it inhibited cell proliferation with an IC 50 value of 0.54μM against OVCAR-8 cells. It could inhibit migration and invasion against OVCAR-8 cells in a concentration-dependent and time-dependent manner. In addition, compound 7c affected the Wnt/β-catenin/GSK3β pathway against ovarian cancer OVCAR-8 cells. In vivo study suggested that compound 7c inhibited tumor growth remarkably without obvious toxicity.Conclusion: In conclusion, benzenesulfonamide hybrid 7c could be a lead compound for further antitumor drug discovery to treat ovarian cancer.Keywords: benzenesulfonamide, proliferation, migration, invasion, in vivo